- DSP - Miscellaneous Signals
- DSP - Classification of DT Signals
- DSP - Classification of CT Signals
- DSP - Basic DT Signals
- DSP - Basic CT Signals
- DSP - Signals-Definition
- DSP - Home
Operations on Signals
- Operations Signals - Convolution
- Operations Signals - Integration
- Operations Signals - Differentiation
- Operations Signals - Reversal
- Operations Signals - Scaling
- Operations Signals - Shifting
Basic System Properties
- DSP - Solved Examples
- DSP - Unstable Systems
- DSP - Stable Systems
- DSP - Time-Variant Systems
- DSP - Time-Invariant Systems
- DSP - Non-Linear Systems
- DSP - Linear Systems
- DSP - Anti-Causal Systems
- DSP - Non-Causal Systems
- DSP - Causal Systems
- DSP - Dynamic Systems
- DSP - Static Systems
Z-Transform
- Z-Transform - Solved Examples
- Z-Transform - Inverse
- Z-Transform - Existence
- Z-Transform - Properties
- Z-Transform - Introduction
Discrete Fourier Transform
- DFT - Solved Examples
- DFT - Discrete Cosine Transform
- DFT - Sectional Convolution
- DFT - Linear Filtering
- DTF - Circular Convolution
- DFT - Time Frequency Transform
- DFT - Introduction
Fast Fourier Transform
Digital Signal Processing Resources
Selected Reading
- Who is Who
- Computer Glossary
- HR Interview Questions
- Effective Resume Writing
- Questions and Answers
- UPSC IAS Exams Notes
DSP - Z-Transform Solved Examples
Example 1
Find the response of the system $s(n+2)-3s(n+1)+2s(n) = delta (n)$, when all the initial conditions are zero.
Solution − Taking Z-transform on both the sides of the above equation, we get
$$S(z)Z^2-3S(z)Z^1+2S(z) = 1$$$Rightarrow S(z)lbrace Z^2-3Z+2 brace = 1$
$Rightarrow S(z) = frac{1}{lbrace z^2-3z+2 brace}=frac{1}{(z-2)(z-1)} = frac{alpha _1}{z-2}+frac{alpha _2}{z-1}$
$Rightarrow S(z) = frac{1}{z-2}-frac{1}{z-1}$
Taking the inverse Z-transform of the above equation, we get
$S(n) = Z^{-1}[frac{1}{Z-2}]-Z^{-1}[frac{1}{Z-1}]$
$= 2^{n-1}-1^{n-1} = -1+2^{n-1}$
Example 2
Find the system function H(z) and unit sample response h(n) of the system whose difference equation is described as under
$y(n) = frac{1}{2}y(n-1)+2x(n)$
where, y(n) and x(n) are the output and input of the system, respectively.
Solution − Taking the Z-transform of the above difference equation, we get
$y(z) = frac{1}{2}Z^{-1}Y(Z)+2X(z)$
$= Y(Z)[1-frac{1}{2}Z^{-1}] = 2X(Z)$
$= H(Z) = frac{Y(Z)}{X(Z)} = frac{2}{[1-frac{1}{2}Z^{-1}]}$
This system has a pole at $Z = frac{1}{2}$ and $Z = 0$ and $H(Z) = frac{2}{[1-frac{1}{2}Z^{-1}]}$
Hence, taking the inverse Z-transform of the above, we get
$h(n) = 2(frac{1}{2})^nU(n)$
Example 3
Determine Y(z),n≥0 in the following case −
$y(n)+frac{1}{2}y(n-1)-frac{1}{4}y(n-2) = 0quad givenquad y(-1) = y(-2) = 1$
Solution − Applying the Z-transform to the above equation, we get
$Y(Z)+frac{1}{2}[Z^{-1}Y(Z)+Y(-1)]-frac{1}{4}[Z^{-2}Y(Z)+Z^{-1}Y(-1)+4(-2)] = 0$
$Rightarrow Y(Z)+frac{1}{2Z}Y(Z)+frac{1}{2}-frac{1}{4Z^2}Y(Z)-frac{1}{4Z}-frac{1}{4} = 0$
$Rightarrow Y(Z)[1+frac{1}{2Z}-frac{1}{4Z^2}] =frac{1}{4Z}-frac{1}{2}$
$Rightarrow Y(Z)[frac{4Z^2+2Z-1}{4Z^2}] = frac{1-2Z}{4Z}$
$Rightarrow Y(Z) = frac{Z(1-2Z)}{4Z^2+2Z-1}$
Advertisements